Chain Extender of Waterborne Polyurethanes Used for Warp Sizing. Issue 1 (January 2014) - Zhu, Zhifeng; Lv, Fuju; Lin, Jack
The effects of chain extender used in the extension of isocyanate-terminated pre-polymer during the preparation of waterborne-polyurethane (WPU) sizes were determined based on properties such as adhesion to fibers, film properties, desizability, and aerobic biodegradability. The extenders used included ethylene glycol (EG), butanediol (BD), hexanediol (HD), and ethylenediamine (EDA). The resulting effects and properties were strongly depended on the extenders. Diols were superior to EDA in increasing the molecular weights of extended WPUs, enhancing the adhesion to polyester fibers, and improving the film properties and aerobic biodegradability. EDA was unsuitable for the extension. For the diols, BD was the most preferred. Comparisons on the properties of the resulting WPUs versus PVA and starch were made.